2018
DOI: 10.1177/2045125318769235
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors for bipolar disorder

Abstract: Bipolar disorder is a multifactorial illness with uncertain aetiology. Knowledge of potential risk factors enables clinicians to identify patients who are more likely to develop bipolar disorder, which directs further investigation, follow up and caution when prescribing. Ideally, identifying directly causative factors for bipolar disorder would enable intervention on an individual or population level to prevent the development of the illness, and improve outcomes through earlier treatment. This article review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
214
4
21

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 368 publications
(248 citation statements)
references
References 146 publications
(214 reference statements)
9
214
4
21
Order By: Relevance
“…Our result of a robust association between cannabis use and prescription of mood stabilizers strengthens the relatively new assumption of cannabis use as a risk factor for bipolar disorder . The effect size for the association between cannabis and mood stabilizers was comparable to the effect size for association between cannabis and antipsychotics, a magnitude similar also to the effect sizes found in studies using a diagnosis of bipolar disorder as outcome .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our result of a robust association between cannabis use and prescription of mood stabilizers strengthens the relatively new assumption of cannabis use as a risk factor for bipolar disorder . The effect size for the association between cannabis and mood stabilizers was comparable to the effect size for association between cannabis and antipsychotics, a magnitude similar also to the effect sizes found in studies using a diagnosis of bipolar disorder as outcome .…”
Section: Discussionsupporting
confidence: 82%
“…While some studies have found that cannabis use increases the risk of first onset of manic symptoms and bipolar disorder by a factor of more than four, others have found the association to be non‐significant after adjustment for confounders . There is a growing conception that cannabis use can act as a risk factor for the onset of bipolar disorder though the causal direction is debated .…”
Section: Introductionmentioning
confidence: 99%
“…Mood disorders are a class of psychiatric illnesses that are defined by the presence of symptoms that severely affect mood . Major depression and bipolar disorder are two common mood disorders, affecting approximately 6% and 2.4% of the world population, respectively. Major depression is characterized by a unipolar depressive state that includes persistent low mood, anhedonia, sleep disturbances and motivational deficiencies, whereas bipolar disorder is uniquely characterized by mood swings between depression, mania and euthymia .…”
mentioning
confidence: 99%
“…Major depression and bipolar disorder are two common mood disorders, affecting approximately 6% and 2.4% of the world population, respectively. Major depression is characterized by a unipolar depressive state that includes persistent low mood, anhedonia, sleep disturbances and motivational deficiencies, whereas bipolar disorder is uniquely characterized by mood swings between depression, mania and euthymia . Cytokine‐mediated inflammatory responses have now emerged as potential contributors to the pathophysiologies of mood disorders .…”
mentioning
confidence: 99%
See 1 more Smart Citation